DALAM MEMUDAHKAN PENGELOLAAN DATA LADA DI BANGKA BELITUNG (MUNTOK WHITE PEPPER) - Atmaja, Eddy Jajang Jaya (LPPM Universitas Malikussaleh - Indonesia, 2022)
ABSTRACTThe Province of the Bangka Belitung Islands has long been known as the main producer and exporter of pepper (Piper nigrum L) in Indonesia. The problem that often arises is the low pepper price that is detrimental to farmers and the price reference that follows the price of the International Pepper Community (IPC). Therefore, the Government established the Bangka Belitung Pepper Joint Marketing Office (KPB) to regulate pepper prices as well as the pepper buying and selling process and ensure that the pepper sent is quality pepper since 2019. KPB has had a positive impact on pepper prices and the pepper trading process and received verified seller and buyer data of pepper. This study aims to examine the role and influence of the Pepper Bangka Belitung Joint Marketing Office (KPB) and the KPB system for pepper farmers, starting from prices, stocks, export data, seller data, buyer data and Geographical Indications (GI) which is a guarantee that the pepper Shipped original from Bangka Belitung.